2019
DOI: 10.29173/istl48
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Selected Bibliographic Database Search Retrieval for Agricultural Information

Abstract: Search result retrieval was compared across eight research literature databases (AGRICOLA, AGRIS, BIOSIS, CAB Direct, FSTA, Google Scholar, Scopus, and Web of Science) for three topics from different agricultural disciplines to compare retrieval results based on searcher experience. Precision, recall, and uniqueness were analyzed by rating search results (~2400 citations) for relevancy. A generalized linear model statistical analysis determined that AGRICOLA ranked highest for precision and was statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Meho and Yang, 2007). The WoS is a multidisciplinary (citation) database that covers “the most significant journals, conference proceedings and books across a range of disciplines including the sciences, social sciences and humanities” (Ritchie et al, 2018) and is considered one of the “two most extensive” and “most widespread [online] databases” of scientific work (Chadegani et al, 2013: 18). Across disciplines, the “ WoS has been used in thousands of published academic studies over the past 20 years” (Li et al, 2018: 1; cf.…”
Section: Review Methodologymentioning
confidence: 99%
“…Meho and Yang, 2007). The WoS is a multidisciplinary (citation) database that covers “the most significant journals, conference proceedings and books across a range of disciplines including the sciences, social sciences and humanities” (Ritchie et al, 2018) and is considered one of the “two most extensive” and “most widespread [online] databases” of scientific work (Chadegani et al, 2013: 18). Across disciplines, the “ WoS has been used in thousands of published academic studies over the past 20 years” (Li et al, 2018: 1; cf.…”
Section: Review Methodologymentioning
confidence: 99%
“…Articles with the same number of connections are grouped in linear clusters around a central point. Data available fromRitchie et al, 2018.…”
mentioning
confidence: 99%
“…There has been some concern around the quality of the data and information gathered through Google Scholar and whether it had been vetted to ensure all the articles are correctly assigned to their authors, which may be a problem for authors with common names. A study done by Ritchie, Banyas, and Sevin found that although Google Scholar provided the most unique content, more than half of it was judged to be not relevant to the author's research output [3]. While using Google Scholar to gather faculty output is a great start, it would be helpful to include other sources.…”
Section: College Of Engineering Faculty Profilesmentioning
confidence: 99%